(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2019)
Ethics has become professional imperative in public relations field, whereby unethical action is not any more considered as integral characteristic of public relations (PR) professionals, especially among scholars and practitioners. However, the question what if public relations professionals really violate ethical standards did not disappear, and concerns every instance linked to the PR-sector. In other words, the question is what disciplinary measures can be taken against the member of PR-associations. This study, based on a qualitative content analysis of websites and statutes of 20 national and international public relations associations from Europe and the US, shows what mechanisms exist in the associations to sanction the unethical behaving of their members. The analysis showed that, unlike international associations that do not take disciplinary action, although the majority of associations has bodies that could provide disciplinary measures (which includes expulsion from membership), only four associations give clear instructions how to make complaints if unethical behaving is detected, and, furthermore, only three associations indicate the consequences of unethical action by publishing judgments on a regular basis. Although the ethics is recognized as crucial principle at declarative level among all associations, efforts of some associations to establish disciplinary committees and to provide real sanctions of unethical professional behavior, can be considered as a progress in defining public relations as a profession with high ethical standards. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.